Optimizing the Utilization of GoFood System Application as an Income Enhancement at Rungkut Surabaya MSME - Invony Dwi Aprilisanda; Devy Sylvia Puspitasari; Luqita Romaisyah (Journal of Economics, Business, and Government Challenges, 2020)
In the digital age, technological developments are moving very fast and changing the lifestyle of humans in general. The technological system in the Digital Age attracted the interests of culinary MSME entrepreneurs in Indonesia to do business with an online sales system. One of the online food delivery service applications in Indonesia is GoFood, this study aims to find out how SMEs in Surabaya as GoFood partners can increase their income by optimizing the use of the GoFood application. This study uses a qualitative method. Data analysis in this research is descriptive qualitative. Criteria for selecting informants using purposive sampling techniques. The interview results state that the GoFood application tends to be easy to use, but some partners regretted the lack of training which resulted in sales not meeting expectations. Quality, Quality, Promo Price, and timeliness of food processing to food delivery to consumers is a strategy for GoFood merchant partners to optimize their sales turnover.